Evaluation of Antibacterial and Antifungal Activity of Herbs Used in Treatment of Diabetes, Malaria and Pneumonia in Kisii and Nyamira Counties Region, Kenya - Moses A. Guto Maobe; Leonard Gitu; Erastus Gatebe (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2021)
The herbs Carissa spinarum, Physalis minima and Toddalia asiatica have traditionally been used in healing diabetes, malaria and pneumonia by the communities around the Kisii region, Kenya. However in the available literature, there is scanty information on effectiveness of different plant parts of the herbs in healing the ailments. The objective of this study was to investigate the potential antimicrobial and antifungal activity of methanolic extract of whole plant Physalis minima, leaf and root of Carissa spinarum and Toddalia asiatica against gram positive bacteria Staphylococcus aureus (ATCC 25923), gram negative bacteria Escherichia coli (ATCC 25922) and fungus Candida albicans (ATCC14053). Antibiotic disc methicillin, cotrimoxazole, chloramphenicol, gentamicin, ampicillin, nalidixic and nitrofurantoin were used in the study. In each herb, plant part was extracted by soaking in methanol/dichloromethane in ratio 1:1 for a week, filtered, concentrated by rotary vapor and cooled. The same process was repeated three times for all samples. The study was conducted by agar well diffusion method. Methanolic root extract of Toddalia asiatica showed highest antibacterial activity against Staphylococcus aureus (ATCC 25923), root extract of Carissa spinarum had highest antibacterial activity against Escherichia coli (ATCC 25922) while root extract of Toddalia asiatica showed highest antifungal activity. It was concluded that root extract of Toddalia asiatica showed highest antibacterial activity 16.7mm against Staphylococcus aureus(ATCC 25923), root extract of Carissa spinarum had highest antibacterial activity 10 mm against Escherichia coli (ATCC 25922) while root extract of Toddalia asiatica had highest antifungal activity 18 mm against Candida albicans.